Compared to what? A three-tiered typology of sustainable development performance indicators from incremental to contextual to transformational - Bill Baue (United Nations Research Institute for Social Development (UNRISD), 2019)
Compared to what? That's the key question this report asks, when it comes to assessing sustainable development performance. So-called sustainable development indicators abound, but do they actually do what they purport to do? Not really, argues Bill Baue in this report: almost no current sustainable development indicators, that is, actually indicate sustainable development. Why not? To answer this question, it helps to ask, compared to what? Current sustainable development indicators typically compare performance to incremental goalposts - less this, less that - which, of course, doesn't actually tell us anything about the sustainability of the impacts. To remedy this, the report invokes the Sustainability Quotient (S = A/N), which compares actual impacts (in the numerator) to normative impacts (in the denominator) to calibrate sustainability.
Keywords: 330